An Injectable Hyaluronic Acid-Based Composite Hydrogel by DA Click Chemistry With pH Sensitive Nanoparticle for Biomedical Application - Hu, Xiaohong; Gao, Ziyu; Tan, Huaping; Wang, Huiming; Mao, Xincheng; Pang, Juan (Frontiers in Chemistry, 2019)
Hydrogels with multifunctional properties attracted intensively attention in the field of tissue engineering because of their excellent performance. Also, object-oriented design had been supposed to an effective and efficient method for material design as cell scaffold in the field of tissue engineering. Therefore, a scaffold-oriented injectable composite hydrogel was constructed by two components. One was pH-sensitive bifunctional nanoparticles for growth factor delivery to improve biofunctionability of hydrogel scaffold. The other was Diels-alder click crosslinked hyaluronic acid hydrogel as matrix. pH dependent release behavior of nanoparticle component was confirmed by results. And, its bioactivity was verified by in vitro cell culture evaluation. In consideration of high-efficiency and effectiveness, low toxicity, controllability and reversibility, dynamic covalent and reversible Diels-alder click chemistry was used to design a HA hydrogel with two kinds of crosslinking points. The properties of hydrogel like gelation time and swelling ratio were influenced by pH value and polymer concentration. Composite hydrogel was formed by in situ polymerization, which exhibited acceptable mechanical property as a scaffold for biomedical field. Lastly, in vitro evaluation from results of viability, DNA content and cell morphology confirmed that hydrogels could maintain cell activity and support cell growth. Compared with pure hydrogel, composite hydrogel possessed better properties.